Semi‐active control algorithms for m-rheological dampers - Braz-César, M.T. (2018)
Structural control includes a wide variety of control methodologies that have been developed over the years to deal with specific problems of civil engineering applications. In this regard, magneto-rheological (MR) dampers seems to be a promising technology to develop semi-active control systems for vibration control of building and bridge structures. Although the application of these devices in actual structures is still emerging, its efficiency to reduce high winds and seismic-induced vibrations has been validated through numerous numerical simulations, experimental tests either in reduced and full scale models and also some real applications. A major challenge of this type of control system is related to the choice of suitable control algorithms that allow the specific features of these controllable devices to be fully exploited. Thus, this paper provides an overview of the fundamental control algorithms usually involved in developing semi‐active controllers with MR dampers for vibration suppression in civil engineering structures. The operating principle of each controller is briefly described specifying for each case the main requirements and also the fundamental control parameters that must be defined during the development of a semi‐active control system with MR dampers.